Una mostra de la transició dialectal catalanoaragonesa: els parlars de la Llitera - Giralt Latorre, Javier (Caplletra. Revista Internacional de Filologia, 1999)
One of the Aragonese areas where there is better evidence of Catalan-Aragonese dialect transition is la Llitera, an area in the province of Osca where Catalan and Aragonese border varieties remain alive, alongside the North-Western varieties proper. In order to show the internal geovariation in the area, this paper presents the most relevant phonetic and morphological traits which may establish the linguistic adscription of the local dialects. This is supported by a number of maps, which allow us to understand the geolinguistic configuration. An appendix includes five ethnotexts representing someof the towns, with a comment on the dialectal words appearing therein.